Integrated detection method for fluidity and accumulation of ceramic shell back layer slurry

Through the integrated detection method of the back layer slurry fluidity and stackability of ceramic shell back layer slurry, the flowability and stackability index of the back layer slurry are measured by a three-dimensional optical detector, which solves the difficulty in quantitative evaluation of the back layer slurry fluidity of ceramic shell back layer slurry fluidity is solved. The problem of this paper improves the uniformity of the thickness of the ceramic shell and the directional solidification quality of the single crystal blade.

CN119246332APending Publication Date: 2025-01-03AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411486494.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The fluidity of the slurry on the back of the ceramic shell is difficult to quantitatively evaluate, resulting in the problem of uneven local stacking and thickness, affecting the uniformity of the thickness of the ceramic shell and the directional solidification of the single crystal blades.

Method used

The integrated detection method of the back layer slurry flowability and stackability of the ceramic shell back layer slurry is used to measure the effective flow area and maximum stacking thickness of the back layer slurry through a three-dimensional optical detector, calculate the flowability and stackability index, and provide quantitative detection results. .

Benefits of technology

The flowability and accumulation properties of the ceramic shell back layer slurry are realized, and the uniformity of the thickness of the ceramic shell is improved, and the single crystal integrity of the single crystal turbine blade is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119246332A_ABST
    Figure CN119246332A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic shell back layer slurry fluidity and accumulation integrated detection method. The method comprises the following steps: pressing a square plate-shaped wax mold; preparing a ceramic shell test plate only coated with a surface layer; preparing a ceramic shell test plate coated with a back layer; selecting a ceramic shell test plate only coated with a surface layer or a ceramic shell test plate coated with a back layer, vertically immersing the part, below the diagonal line, of the ceramic shell test plate into the back layer slurry for slurry dipping and slurry control, overturning the ceramic shell test plate by 180 degrees, hanging, drying and slurry control, and thus obtaining a flowability test plate to be tested; and measuring the effective flow area and the maximum accumulation thickness of the back layer slurry below the boundary on the fluidity test plate to be measured and the total volume of the back layer slurry above the boundary by using a three-dimensional optical detector, and calculating the fluidity index and the accumulation index of the back layer slurry. According to the method, the fluidity and accumulation degree of the ceramic shell back layer slurry can be intuitively evaluated, and data support is provided for thickness uniformity control of the ceramic shell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic shell back layer slurry detection, and in particular relates to an integrated detection method for fluidity and stacking properties of ceramic shell back layer slurry. Background Art

[0002] As we all know, the turbine blades for aircraft engines are known as the jewel in the crown of modern industry. The materials of turbine blades have evolved from the initial equiaxed crystal casting high-temperature alloy to the directional solidification columnar crystal high-temperature alloy, and now to the single crystal high-temperature alloy. Single crystal high-temperature alloy turbine blades are made by precision casting, which has many preparation steps and a long preparation process. The ceramic shell is used as a container for the directional solidification of single crystal high-temperature alloy turbine blades. It needs to serve for 1-3 hours at above 1500℃ and under the high-temperature alloy liquid load. During the service process, sufficient strength and a stable temperature field must be guaranteed to meet the needs of directional growth of single crystal blades.

[0003] The ceramic shell is formed by coating slurry and sand layer by layer, among which the surface slurry is the key factor affecting the quality of the inner surface of the ceramic shell, and the large amount (i.e., multiple layers) of back layer slurry is the key factor affecting the uniformity of the thickness of the ceramic shell. Due to the diversity of the blade wax mold structure, the thickness of the back layer slurry of the ceramic shell is not consistent on the blade wax mold, which leads to uneven thickness of the final ceramic shell at different structures. Generally speaking, it is not easy to coat the slurry on the exhaust edge, edge plate and other positions of the blade, and the shell at the corresponding position is often thin. At the same time, the edge plate is a position that is prone to premature nucleation during the directional solidification of the single crystal working blade. A thin shell at this position will aggravate the premature solidification of this position, thereby causing the edge plate to produce stray crystals and aggravate scrapping. It can be seen that the control of the uniformity of the thickness of the back layer slurry of the ceramic shell is of great significance to the directional solidification of the single crystal blade.

[0004] The thickness of the ceramic shell is determined by the accumulation of ceramic shell slurry and sand layer by layer. The slurry is the direct material for coating the ceramic shell. The uniformity of the thickness of each layer will affect the overall thickness of the ceramic shell. Routine tests of the back layer slurry of the ceramic shell include viscosity, pH value, board weight, solid content, etc. These test indicators have a good characterization capability for the process consistency and stability of the back layer slurry of the ceramic shell. Among them, viscosity and board weight can characterize the coating characteristics of the back layer slurry in an overall and macroscopic way. Viscosity refers to the outflow time of the slurry through the standard flow cup. The shorter the outflow time, the better the slurry fluidity; board weight refers to the coating weight of the slurry on the standard test plate, which can characterize the overall average thickness of the slurry coating. However, it was found in production practice that even at the same viscosity, the fluidity of the slurry varies significantly, especially the fluidity of the ceramic shell back layer slurry on the upper layer of slurry / sand is difficult to quantitatively evaluate, and uneven problems such as local piling and local thinning often occur. Therefore, there is an urgent need to develop an integrated detection method for the fluidity and stacking of the ceramic shell back layer slurry. This method can intuitively and quantitatively detect the fluidity and stacking of the back layer slurry. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides an integrated detection method for the fluidity and stacking properties of a ceramic shell back layer slurry. The integrated detection method comprises the following steps in chronological order:

[0006] Step 1: Use a wax pressing machine to press several square plate wax models. After the pressing is completed, use a wax model special cleaning agent to clean the square plate wax models and dry them for later use;

[0007] Step 2: Prepare the ceramic shell surface slurry, and carry out four surface coating processes of slurry dipping, slurry control, sand pouring, and drying on the square plate wax mold. After the surface coating process is completed, the ceramic shell test plate with only the surface layer coated is obtained;

[0008] Step 3: Prepare the ceramic shell back layer slurry, and perform four back layer coating processes of slurry dipping, slurry control, sand pouring, and drying on the prepared ceramic shell test plate coated with only the surface layer. After the back layer coating process is completed, the ceramic shell test plate coated with the back layer is obtained; if the ceramic shell test plate coated with different number of back layers is to be prepared, it is necessary to repeat the four back layer coating processes of slurry dipping, slurry control, sand pouring, and drying until the ceramic shell test plate coated with the required number of back layers is obtained;

[0009] Step 4: Select a ceramic shell test plate coated with only the surface layer or a ceramic shell test plate coated with the back layer, take the diagonal line of the ceramic shell test plate as the dividing line, keep the dividing line in a horizontal state, vertically immerse the part of the ceramic shell test plate below the dividing line into the back layer slurry for slurry dipping, and after the slurry dipping is completed, vertically take out the ceramic shell test plate and control the slurry; after the slurry control is completed, turn the ceramic shell test plate 180 degrees and hang it for drying. During the drying process, keep the dividing line in a horizontal state, and the back layer slurry is naturally controlled downward by gravity. After the drying is completed, the fluidity test plate to be tested is obtained;

[0010] Step 5: Use a 3D optical detector to scan the ceramic shell test plate and the fluidity test plate to be tested, and use the ceramic shell test plate as a reference to analyze the 3D size and maximum stacking thickness of the back layer slurry on the fluidity test plate to be tested;

[0011] Step 6: measuring the effective flow area of ​​the back layer slurry below the dividing line on the fluidity test plate to be tested, and calculating the fluidity index of the back layer slurry according to the fluidity index model of the back layer slurry;

[0012] Step 7: Measure the maximum stacking thickness of the back layer slurry below the dividing line and the total volume of the back layer slurry above the dividing line on the fluidity test plate to be tested, and calculate the stacking index of the back layer slurry according to the stacking index model of the back layer slurry.

[0013] Preferably, in step one, the side length of the square plate-shaped wax mold is 50-200 mm and the thickness is 3-20 mm; the pressing parameters of the square plate-shaped wax mold are wax injection temperature 60-70°C, wax injection pressure 5-15 bar, and holding time 20-40s.

[0014] In any of the above schemes, preferably, in step 1, the drying parameters of the square plate-shaped wax model are: ambient temperature 21±2° C., ambient humidity 50±10%, wind speed not higher than 1 m / s, and drying time not less than 4 h.

[0015] In any of the above schemes, preferably, in step 2, the ceramic shell surface layer slurry includes any one of zircon powder slurry, white corundum slurry, mullite slurry, and precision casting ceramic shell surface layer slurry containing a refiner, and the viscosity of the ceramic shell surface layer slurry is 20-30s.

[0016] In any of the above schemes, preferably, in step 2, the sand showering process selects 80-mesh or 100-mesh corundum sand; the drying process parameters are: ambient temperature 21±2° C., ambient humidity 50±10%, wind speed not higher than 1 m / s, and drying time 4-8 h.

[0017] In any of the above schemes, preferably, in step three, the ceramic shell back layer slurry includes any one of zircon powder slurry, white corundum slurry, mullite slurry, and fused quartz slurry, and the viscosity of the ceramic shell back layer slurry is 10-20s.

[0018] In any of the above schemes, it is preferred that in step three, the sand showering process selects 80 mesh, 60 mesh, 46 mesh, 30 mesh or 24 mesh corundum sand; the drying process parameters are ambient temperature 21±2°C, ambient humidity 40±10%, wind speed 2-6m / s, and drying time 4-8h.

[0019] In any of the above schemes, preferably, in step four, the portion of the ceramic shell test plate below the dividing line is vertically immersed in the back layer slurry for dipping, and the dipping time is 15-45s; after the dipping is completed, the ceramic shell test plate is vertically taken out and the slurry is controlled, and the slurry control time is 10-15s; the ceramic shell test plate is turned over 180 degrees and hung to dry, the ambient temperature is 21±2℃, the ambient humidity is 40±10%, the wind speed is not higher than 1m / s, and the drying time is 2-4h.

[0020] In any of the above schemes, preferably, in step 6, the fluidity index model of the backing layer slurry is Where:

[0021] f——fluidity index of backing slurry, dimensionless;

[0022] S——Effective flow area of ​​backing slurry, mm 2 ;

[0023] l——side length of square plate wax model, mm.

[0024] In any of the above schemes, preferably, in step 7, the packing index model of the backing layer slurry is Where:

[0025] a——the packing index of the backing slurry, dimensionless;

[0026] d——maximum accumulation thickness of backing slurry, mm;

[0027] l——side length of square wax model, mm;

[0028] V——The total volume of the backing slurry above the dividing line on the fluidity test plate to be tested, mm 3 .

[0029] In the present invention, the wax pressing machine, three-dimensional optical detector, etc. used are all traditional equipment, and there are no special requirements for the structure and model of the equipment. In step 1, the pressing process of the square plate wax mold is a traditional process, and there are no special requirements for the process flow, process parameters and pressing equipment. It is only necessary to ensure that several key pressing parameters such as wax injection temperature, wax injection pressure, and holding time meet the requirements of the present invention; the wax material used is also a traditional wax material, such as F28 wax material.

[0030] In step two, the components and preparation process of the ceramic shell surface layer slurry are all traditional technologies, and there are no special requirements for the raw materials and their proportions, the process flow and its process parameters. The coating process of the ceramic shell surface layer slurry includes slurry dipping, slurry control, sand pouring and drying. These processes are all operated using traditional processes, and there are no special requirements for the process flow, process parameters and equipment used. It is only necessary to control the viscosity of the ceramic shell surface layer slurry to 20-30s (Zahn 4# flow cup).

[0031] In step three, the components and preparation process of the ceramic shell back layer slurry are all traditional technologies, and there are no special requirements for the raw materials and their proportions, the process flow and its process parameters. The coating process of the ceramic shell back layer slurry includes dipping, controlling, sanding and drying. These processes are all operated using traditional processes, and there are no special requirements for the process flow, process parameters and equipment used. It is only necessary to control the viscosity of the ceramic shell back layer slurry to 10-20s (Zahn 4# flow cup).

[0032] In step 4, for the same backing layer slurry to be tested, at least five fluidity test plates are prepared for subsequent comparative analysis, because even for the same backing layer slurry, its fluidity and stacking properties will vary for different test plates, so multiple test plates need to be tested and analyzed.

[0033] In step 6, the fluidity index of the backing layer slurry is a macroscopic, holistic index with good stability. The larger the fluidity index of the backing layer slurry, the larger the effective flow area of ​​the backing layer slurry, the better the fluidity of the backing layer slurry, and the more uniform the flow.

[0034] In step seven, the larger the stacking index of the back layer slurry is, the greater the maximum stacking thickness of the back layer slurry is, and the worse the fluidity of the back layer slurry is, the easier it is for the slurry to stack.

[0035] The integrated detection method for fluidity and stacking properties of ceramic shell back layer slurry of the present invention has the following beneficial effects:

[0036] (1) In order to solve the problem that the fluidity of the back layer slurry of the ceramic shell lacks a quantitative evaluation method and thus affects the control of the uniformity of the thickness of the ceramic shell, the present invention uses a three-dimensional optical measuring instrument to quantitatively measure the effective flow area and the maximum stacking thickness of the back layer slurry below the dividing line on the fluidity test plate to be tested, detects the fluidity of the back layer slurry based on the effective flow area, and detects the stacking property of the back layer slurry based on the maximum stacking thickness.

[0037] (2) The detection method of the present invention has the characteristics of intuitive detection effect, accurate and quantitative detection results, and strong engineering significance of detection data. It can intuitively and effectively evaluate the fluidity and stacking degree of the ceramic shell back layer slurry, provide process data support for the control of ceramic shell thickness uniformity, and effectively improve the single crystal integrity compliance of single crystal turbine blades.

[0038] (3) The detection method of the present invention is applicable to the fluidity detection of each backing layer slurry starting from the second layer, and the ceramic shell test plate can be in the state of being coated with one layer or any layer.

[0039] (4) The present invention can prepare ceramic shell test plates with a variety of back layer slurries and sand materials in advance. The detection method of the present invention can realize a horizontal comparative analysis of the fluidity of different back layer slurries, and can also be used for consistency inspection of the fluidity of multiple batches of back layer slurries. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a flow chart of a preferred embodiment of the integrated detection method of the fluidity and stacking property of the ceramic shell back layer slurry according to the present invention;

[0041] Figure 2 for Figure 1 A schematic diagram of the preparation process of the test plate to be tested for fluidity in the embodiment shown;

[0042] Figure 3 for Figure 1 The three-dimensional dimension measurement diagram of the backing layer slurry on the 1# fluidity test plate to be tested in the embodiment shown;

[0043] Figure 4 for Figure 1 The three-dimensional dimension measurement diagram of the backing layer slurry on the 2# fluidity test plate to be tested in the embodiment shown;

[0044] Figure 5 for Figure 1 The three-dimensional dimension measurement diagram of the backing layer slurry on the 3# fluidity test plate to be tested in the embodiment shown;

[0045] Figure 6 for Figure 1 The three-dimensional dimension measurement diagram of the backing layer slurry on the 4# fluidity test plate to be tested in the embodiment shown;

[0046] Figure 7 for Figure 1 The three-dimensional dimension measurement diagram of the backing layer slurry on the 5# fluidity test plate to be tested in the embodiment shown;

[0047] Figure 8 for Figure 1 The maximum stacking thickness measurement diagram of the backing slurry on the 1# fluidity test plate to be tested in the embodiment shown;

[0048] Fig. 9 for Figure 1 The maximum stacking thickness measurement diagram of the backing slurry on the 2# fluidity test plate to be tested in the embodiment shown;

[0049] Fig.10 for Figure 1 The maximum stacking thickness measurement diagram of the backing slurry on the 3# fluidity test plate to be tested in the embodiment shown;

[0050] Fig.11 for Figure 1 The maximum stacking thickness measurement diagram of the backing slurry on the 4# fluidity test plate to be tested in the embodiment shown;

[0051] Fig.12 for Figure 1 The maximum stacking thickness measurement diagram of the backing layer slurry on the 5# fluidity test plate to be tested in the embodiment shown.

[0052] Notes in the figure: 1-ceramic shell test plate, 2-dividing line, 3-back layer slurry. DETAILED DESCRIPTION

[0053] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.

[0054] Embodiment 1:

[0055] like Figure 1 As shown, according to a preferred embodiment of the integrated detection method for the fluidity and stacking properties of the ceramic shell back layer slurry of the present invention, the integrated detection method includes the following steps in chronological order:

[0056] Step 1: Use a wax pressing machine to press several square plate wax models. After the pressing is completed, use a wax model special cleaning agent to clean the square plate wax models and dry them for later use;

[0057] Step 2: Prepare the ceramic shell surface slurry, and carry out four surface coating processes of slurry dipping, slurry control, sand pouring, and drying on the square plate wax mold. After the surface coating process is completed, the ceramic shell test plate with only the surface layer coated is obtained;

[0058] Step 3: Prepare the ceramic shell back layer slurry, and perform four back layer coating processes of slurry dipping, slurry control, sand pouring, and drying on the prepared ceramic shell test plate coated with only the surface layer. After the back layer coating process is completed, the ceramic shell test plate coated with the back layer is obtained; if the ceramic shell test plate coated with different number of back layers is to be prepared, it is necessary to repeat the four back layer coating processes of slurry dipping, slurry control, sand pouring, and drying until the ceramic shell test plate coated with the required number of back layers is obtained;

[0059] Step 4: Select a ceramic shell test plate coated with only the surface layer or a ceramic shell test plate coated with the back layer, take the diagonal line of the ceramic shell test plate 1 as the dividing line 2, keep the dividing line 2 in a horizontal state, and vertically immerse the part of the ceramic shell test plate 1 below the dividing line 2 into the back layer slurry 3 for slurry dipping. After the slurry dipping is completed, vertically take out the ceramic shell test plate 1 and control the slurry; after the slurry control is completed, turn the ceramic shell test plate 1 180 degrees and hang it to dry. During the drying process, keep the dividing line 2 in a horizontal state, and the back layer slurry 3 is naturally controlled downward by gravity. After the drying is completed, the fluidity test plate to be tested is obtained. The schematic diagram of the preparation process of the fluidity test plate to be tested is shown in the figure. Figure 2 As shown;

[0060] Step 5: Use a 3D optical detector to scan the ceramic shell test plate and the fluidity test plate to be tested, and use the ceramic shell test plate as a reference to analyze the 3D size and maximum stacking thickness of the back layer slurry on the fluidity test plate to be tested;

[0061] Step 6: measuring the effective flow area of ​​the back layer slurry below the dividing line on the fluidity test plate to be tested, and calculating the fluidity index of the back layer slurry according to the fluidity index model of the back layer slurry;

[0062] Step 7: Measure the maximum stacking thickness of the back layer slurry below the dividing line and the total volume of the back layer slurry above the dividing line on the fluidity test plate to be tested, and calculate the stacking index of the back layer slurry according to the stacking index model of the back layer slurry.

[0063] In step four of this embodiment, a ceramic shell test plate with only a surface layer coated is selected to prepare a fluidity test plate to be tested. A total of five fluidity test plates to be tested are prepared and are numbered: 1# fluidity test plate to be tested, 2# fluidity test plate to be tested, 3# fluidity test plate to be tested, 4# fluidity test plate to be tested, and 5# fluidity test plate to be tested.

[0064] In step 1, the side length of the square plate wax mold is 100 mm and the thickness is 10 mm; the pressing parameters of the square plate wax mold are: wax injection temperature 65°C, wax injection pressure 10 bar, and holding time 30 seconds. The drying parameters of the square plate wax mold are: ambient temperature 21±2°C, ambient humidity 50±10%, wind speed not higher than 1m / s, and drying time 4h.

[0065] In step 2, the ceramic shell surface slurry is white corundum slurry, and the viscosity of the ceramic shell surface slurry is 25s. The sanding process selects 80-mesh corundum sand; the drying process parameters are: ambient temperature 21±2°C, ambient humidity 50±10%, wind speed not higher than 1m / s, and drying time 6h.

[0066] In step 4, prepare the back layer slurry of the ceramic shell, and select white corundum slurry with a viscosity of 15s. The part of the ceramic shell test plate below the dividing line is vertically immersed in the back layer slurry for slurry dipping, and the slurry dipping time is 30s; after the slurry dipping is completed, the ceramic shell test plate is vertically taken out and the slurry is controlled, and the slurry control time is 12s; the ceramic shell test plate is turned 180 degrees and hung to dry, the ambient temperature is 21±2℃, the ambient humidity is 40±10%, the wind speed is not higher than 1m / s, and the drying time is 3h.

[0067] In step 6, the fluidity index model of the backing slurry is Where:

[0068] f——fluidity index of backing slurry, dimensionless;

[0069] S——Effective flow area of ​​backing slurry, mm 2 ;

[0070] l——side length of square plate wax model, mm.

[0071] In step 7, the packing index model of the backing layer slurry is Where:

[0072] a——the packing index of the backing slurry, dimensionless;

[0073] d——maximum accumulation thickness of backing slurry, mm;

[0074] l——side length of square wax model, mm;

[0075] V——The total volume of the backing slurry above the dividing line on the fluidity test plate to be tested, mm 3 .

[0076] In this embodiment, the three-dimensional dimensions and maximum stacking thickness of the backing slurry on five fluidity test plates to be tested are measured, wherein the three-dimensional dimensions of the backing slurry on the five fluidity test plates to be tested are as follows: Figure 3-7 As shown in the figure, the maximum stacking thickness of the backing slurry on the five fluidity test plates is as follows: Figure 8-12 The test results of the fluidity of the back layer slurry are shown in Table 1, and the test results of the stacking of the back layer slurry are shown in Table 2.

[0077] Table 1 Back layer slurry fluidity test results

[0078]

[0079] Table 2 Back layer slurry accumulation test results

[0080]

[0081] In this embodiment, the wax pressing machine, three-dimensional optical detector, etc. used are all traditional equipment, and there are no special requirements for the structure and model of the equipment. In step 1, the pressing process of the square plate wax mold is a traditional process, and there are no special requirements for the process flow, process parameters and pressing equipment. It is only necessary to ensure that several key pressing parameters such as wax injection temperature, wax injection pressure, and holding time meet the requirements of the present invention; the wax material used is F28 wax material.

[0082] In step two, the components and preparation process of the ceramic shell surface layer slurry are all traditional technologies, and there are no special requirements for the raw materials and their proportions, the process flow and its process parameters. The coating process of the ceramic shell surface layer slurry includes slurry dipping, slurry control, sand pouring and drying. These processes are all operated using traditional processes, and there are no special requirements for the process flow, process parameters and equipment used. It is only necessary to control the viscosity of the ceramic shell surface layer slurry to 20-30s (Zahn 4# flow cup).

[0083] In step 4, the components and preparation process of the ceramic shell backing slurry are all traditional technologies, and there are no special requirements for the raw materials and their ratios, process flow and process parameters, etc. It is only necessary to control the viscosity of the ceramic shell backing slurry to 10-20s (Zahn 4# flow cup). For the same backing slurry to be tested, five fluidity test plates to be tested are prepared for subsequent comparative analysis.

[0084] In step 6, the fluidity index of the backing layer slurry is a macroscopic, holistic index with good stability. The larger the fluidity index of the backing layer slurry, the larger the effective flow area of ​​the backing layer slurry, the better the fluidity of the backing layer slurry, and the more uniform the flow.

[0085] In step seven, the larger the stacking index of the back layer slurry is, the greater the maximum stacking thickness of the back layer slurry is, and the worse the fluidity of the back layer slurry is, the easier it is for the slurry to stack.

[0086] The integrated detection method for the fluidity and stacking property of the back layer slurry of the ceramic shell of this embodiment has the following beneficial effects: (1) In view of the problem that the fluidity of the back layer slurry of the ceramic shell lacks a quantitative evaluation method and affects the control of the uniformity of the thickness of the ceramic shell, a three-dimensional optical measuring instrument is used to quantitatively measure the effective flow area and the maximum stacking thickness of the back layer slurry below the dividing line on the fluidity test plate to be tested, and the fluidity of the back layer slurry is detected according to the effective flow area, and the stacking property of the back layer slurry is detected according to the maximum stacking thickness. (2) The detection method can intuitively and effectively evaluate the fluidity and stacking degree of the back layer slurry of the ceramic shell, provide process data support for the control of the uniformity of the thickness of the ceramic shell, and effectively improve the single crystal integrity compliance of the single crystal turbine blade. (3) The detection method is applicable to the fluidity detection of each layer of the back layer slurry starting from the second layer, and the ceramic shell test plate can be in the state of coating one layer or any layer. (4) Ceramic shell test plates with a variety of back layer slurries and sand materials can be prepared in advance. Through this detection method, a horizontal comparative analysis of the fluidity of different back layer slurries can be achieved, and it can also be used for the consistency inspection of the fluidity of multiple batches of back layer slurries.

[0087] Embodiment 2:

[0088] According to another preferred embodiment of the integrated detection method of the fluidity and stacking property of the ceramic shell back layer slurry of the present invention, its detection process, calculation model, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0089] In step 4 of this embodiment, a ceramic shell test plate coated with a back layer is selected to prepare a fluidity test plate to be tested.

[0090] In step 1, the side length of the square plate wax mold is 50 mm and the thickness is 3 mm; the pressing parameters of the square plate wax mold are: wax injection temperature 60°C, wax injection pressure 5 bar, and holding time 20 seconds. The drying parameters of the square plate wax mold are: ambient temperature 21±2°C, ambient humidity 50±10%, wind speed not higher than 1m / s, and drying time 4h.

[0091] In step 2, the ceramic shell surface slurry is white corundum slurry, and the viscosity of the ceramic shell surface slurry is 20s. The sanding process selects 100-mesh corundum sand; the drying process parameters are: ambient temperature 21±2°C, ambient humidity 50±10%, wind speed not higher than 1m / s, and drying time 4h.

[0092] In step three, the ceramic shell back layer slurry is white corundum slurry, and the viscosity of the ceramic shell back layer slurry is 10s. The sand pouring process selects 80 mesh corundum sand; the drying process parameters are ambient temperature 21±2°C, ambient humidity 40±10%, wind speed 2m / s, and drying time 4h. The components and preparation process of the ceramic shell back layer slurry are all traditional technologies, and there are no special requirements for raw materials and their proportions, process flow and process parameters; the coating process of the ceramic shell back layer slurry includes slurry dipping, slurry control, sand pouring and drying, etc. These processes are all operated using traditional processes, and there are no special requirements for process flow, process parameters and equipment used. It is only necessary to control the viscosity of the ceramic shell back layer slurry to 10-20s (Zahn 4# flow cup).

[0093] In step four, the part of the ceramic shell test plate below the dividing line is vertically immersed in the back layer slurry for dipping, and the dipping time is 15 seconds; after the dipping is completed, the ceramic shell test plate is vertically taken out and the slurry is controlled for 10 seconds; the ceramic shell test plate is turned over 180 degrees and hung to dry, the ambient temperature is 21±2°C, the ambient humidity is 40±10%, the wind speed is not higher than 1m / s, and the drying time is 2h.

[0094] Embodiment three:

[0095] According to another preferred embodiment of the integrated detection method of the fluidity and stacking property of the ceramic shell back layer slurry of the present invention, its detection process, calculation model, technical principle, beneficial effects, etc. are basically the same as those of the first embodiment, except that:

[0096] In step 4 of this embodiment, a ceramic shell test plate coated with three back layers is selected to prepare a fluidity test plate to be tested.

[0097] In step 1, the side length of the square plate wax mold is 200 mm and the thickness is 20 mm; the pressing parameters of the square plate wax mold are: wax injection temperature 70°C, wax injection pressure 15 bar, and holding time 40 seconds. The drying parameters of the square plate wax mold are: ambient temperature 21±2°C, ambient humidity 50±10%, wind speed not higher than 1m / s, and drying time 4 hours.

[0098] In step 2, the ceramic shell surface slurry is white corundum slurry, and the viscosity of the ceramic shell surface slurry is 30s. The sanding process selects 100-mesh corundum sand; the drying process parameters are: ambient temperature 21±2°C, ambient humidity 50±10%, wind speed not higher than 1m / s, and drying time 8h.

[0099] In step three, the ceramic shell back layer slurry is white corundum slurry, and the viscosity of the ceramic shell back layer slurry is 20s. The sand pouring process selects 30 mesh corundum sand; the drying process parameters are ambient temperature 21±2°C, ambient humidity 40±10%, wind speed 6m / s, and drying time 8h. The components and preparation process of the ceramic shell back layer slurry are all traditional technologies, and there are no special requirements for raw materials and their proportions, process flow and process parameters; the coating process of the ceramic shell back layer slurry includes slurry dipping, slurry control, sand pouring and drying, etc. These processes are all operated using traditional processes, and there are no special requirements for process flow, process parameters and equipment used. It is only necessary to control the viscosity of the ceramic shell back layer slurry to 10-20s (Zahn 4# flow cup).

[0100] In step four, the part of the ceramic shell test plate below the dividing line is vertically immersed in the back layer slurry for dipping, and the dipping time is 45 seconds; after the dipping is completed, the ceramic shell test plate is vertically taken out and the slurry is controlled for 15 seconds; the ceramic shell test plate is turned over 180 degrees and hung to dry, the ambient temperature is 21±2°C, the ambient humidity is 40±10%, the wind speed is not higher than 1m / s, and the drying time is 4h.

[0101] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.

[0102] It is not difficult for those skilled in the art to understand that the integrated detection method for the fluidity and stacking property of the back layer slurry of the ceramic shell of the present invention includes any combination of the invention content and specific implementation mode of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An integrated detection method for fluidity and stacking of ceramic shell back layer slurry, characterized in that: The integrated detection method comprises the following steps in chronological order: Step 1: Use a wax pressing machine to press several square plate wax models. After the pressing is completed, use a wax model special cleaning agent to clean the square plate wax models and dry them for later use; Step 2: Prepare the ceramic shell surface slurry, and carry out four surface coating processes of slurry dipping, slurry control, sand pouring, and drying on the square plate wax mold. After the surface coating process is completed, the ceramic shell test plate with only the surface layer coated is obtained; Step 3: Prepare the ceramic shell back layer slurry, and perform four back layer coating processes of slurry dipping, slurry control, sand pouring, and drying on the prepared ceramic shell test plate coated with only the surface layer. After the back layer coating process is completed, the ceramic shell test plate coated with the back layer is obtained; if the ceramic shell test plate coated with different number of back layers is to be prepared, it is necessary to repeat the four back layer coating processes of slurry dipping, slurry control, sand pouring, and drying until the ceramic shell test plate coated with the required number of back layers is obtained; Step 4: Select a ceramic shell test plate coated with only the surface layer or a ceramic shell test plate coated with the back layer, take the diagonal line of the ceramic shell test plate as the dividing line, keep the dividing line in a horizontal state, vertically immerse the part of the ceramic shell test plate below the dividing line into the back layer slurry for slurry dipping, and after the slurry dipping is completed, vertically take out the ceramic shell test plate and control the slurry; after the slurry control is completed, turn the ceramic shell test plate 180 degrees and hang it for drying. During the drying process, keep the dividing line in a horizontal state, and the back layer slurry is naturally controlled downward by gravity. After the drying is completed, the fluidity test plate to be tested is obtained; Step 5: Use a 3D optical detector to scan the ceramic shell test plate and the fluidity test plate to be tested, and use the ceramic shell test plate as a reference to analyze the 3D size and maximum stacking thickness of the back layer slurry on the fluidity test plate to be tested; Step 6: measuring the effective flow area of ​​the back layer slurry below the dividing line on the fluidity test plate to be tested, and calculating the fluidity index of the back layer slurry according to the fluidity index model of the back layer slurry; Step 7: Measure the maximum stacking thickness of the back layer slurry below the dividing line and the total volume of the back layer slurry above the dividing line on the fluidity test plate to be tested, and calculate the stacking index of the back layer slurry according to the stacking index model of the back layer slurry.

2. The integrated detection method for fluidity and stacking properties of ceramic shell backing slurry according to claim 1, characterized in that: In step 1, the side length of the square plate-shaped wax mold is 50-200 mm and the thickness is 3-20 mm; the pressing parameters of the square plate-shaped wax mold are wax injection temperature 60-70°C, wax injection pressure 5-15 bar, and holding time 20-40s.

3. The integrated detection method for fluidity and stacking properties of ceramic shell back layer slurry according to claim 2, characterized in that: In step 1, the drying parameters of the square plate-shaped wax model are: ambient temperature 21±2° C., ambient humidity 50±10%, wind speed not higher than 1 m / s, and drying time not less than 4 hours.

4. The integrated detection method for fluidity and stacking properties of ceramic shell back layer slurry according to claim 3, characterized in that: In step 2, the ceramic shell surface layer slurry includes any one of zircon powder slurry, white corundum slurry, mullite slurry, and precision casting ceramic shell surface layer slurry containing a refiner, and the viscosity of the ceramic shell surface layer slurry is 20-30s.

5. The integrated detection method for fluidity and stacking properties of ceramic shell backing slurry according to claim 4, characterized in that: In step 2, the sand shower process selects 80 mesh or 100 mesh corundum sand; the drying process parameters are: ambient temperature 21±2°C, ambient humidity 50±10%, wind speed not higher than 1m / s, and drying time 4-8h.

6. The integrated detection method for fluidity and stacking properties of ceramic shell back layer slurry according to claim 5, characterized in that: In step three, the ceramic shell back layer slurry includes any one of zircon powder slurry, white corundum slurry, mullite slurry, and fused quartz slurry, and the viscosity of the ceramic shell back layer slurry is 10-20s.

7. The integrated detection method for fluidity and stacking properties of ceramic shell backing slurry according to claim 6, characterized in that: In step three, the sand showering process selects 80 mesh, 60 mesh, 46 mesh, 30 mesh or 24 mesh corundum sand; the drying process parameters are: ambient temperature 21±2°C, ambient humidity 40±10%, wind speed 2-6m / s, and drying time 4-8h.

8. The integrated detection method for fluidity and stacking properties of ceramic shell backing slurry according to claim 7, characterized in that: In step four, the part of the ceramic shell test plate below the dividing line is vertically immersed in the back layer slurry for dipping, and the dipping time is 15-45s; after the dipping is completed, the ceramic shell test plate is vertically taken out and the slurry is controlled, and the slurry control time is 10-15s; the ceramic shell test plate is turned over 180 degrees and hung to dry, the ambient temperature is 21±2℃, the ambient humidity is 40±10%, the wind speed is not higher than 1m / s, and the drying time is 2-4h.

9. The integrated detection method for fluidity and stacking properties of ceramic shell backing slurry according to claim 8, characterized in that: In step 6, the fluidity index model of the backing slurry is In the formula, f——fluidity index of backing slurry, dimensionless; S——Effective flow area of ​​backing slurry, mm 2 ; l——side length of square plate wax model, mm.

10. The integrated detection method for fluidity and stacking properties of ceramic shell backing slurry according to claim 9, characterized in that: In step 7, the packing index model of the backing layer slurry is In the formula, a——the packing index of the backing slurry, dimensionless; d——maximum accumulation thickness of backing slurry, mm; l——side length of square wax model, mm; V——The total volume of the backing slurry above the dividing line on the fluidity test plate to be tested, mm 3 .